Altered brain morphology in boys with attention deficit hyperactivity disorder with and without comorbid conduct disorder/oppositional defiant disorder. Issue 4 (5th November 2019) - Vetter, Nora C.; Backhausen, Lea L.; Buse, Judith; Roessner, Veit; Smolka, Michael N.
Abstract: About 50% of attention deficit hyperactivity disorder (ADHD) patients suffer from comorbidity with oppositional defiant disorder/conduct disorder (ODD/CD). Most previous studies on structural morphology did not differentiate between pure (ADHD‐only) and comorbid ADHD (ADHD+ODD/CD). Therefore, we aimed to investigate the structural profile of ADHD‐only versus ADHD+ODD/CD spanning the indices subcortical and cortical volume, cortical thickness, and surface area. We predicted a reduced total gray matter, striatal, and cerebellar volume in both patient groups and a reduced amygdalar and hippocampal volume for ADHD+ODD/CD. We also explored alterations in prefrontal volume, thickness, and surface area. We acquired structural images from an adolescent sample ranging from 11 to 17 years, matched with regard to age, pubertal status, and IQ—including 36 boys with ADHD‐only, 26 boys with ADHD+ODD/CD, and 30 typically developing (TD) boys. We analyzed structural data with FreeSurfer. We found reductions in total gray matter and total surface area for both patient groups. Boys with ADHD+ODD/CD had a thicker cortex than the other groups in a right rostral middle frontal cluster, which was related to stronger ODD/CD symptoms, even when controlling for ADHD symptoms. No group differences in local cortical volume or surface area emerged. We demonstrate the necessity to carefully differentiate between ADHD and ADHD+ODD/CD. The increased rostral middle frontal thickness might hint at a delayed adolescent cortical thinning in ADHD+ODD/CD. Patients with the double burden ADHD and ODD or CD seem to be even more affected than patients with pure ADHD.